Human neural stem cell‐derived cultures in three‐dimensional substrates form spontaneously functional neuronal networks. (25th February 2015) - Smith, Imogen; Silveirinha, Vasco; Stein, Jason L.; de la Torre‐Ubieta, Luis; Farrimond, Jonathan A.; Williamson, Elizabeth M.; Whalley, Benjamin J.
Abstract: Differentiated human neural stem cells were cultured in an inert three‐dimensional (3D) scaffold and, unlike two‐dimensional (2D) but otherwise comparable monolayer cultures, formed spontaneously active, functional neuronal networks that responded reproducibly and predictably to conventional pharmacological treatments to reveal functional, glutamatergic synapses. Immunocytochemical and electron microscopy analysis revealed a neuronal and glial population, where markers of neuronal maturity were observed in the former. Oligonucleotide microarray analysis revealed substantial differences in gene expression conferred by culturing in a 3D vs a 2D environment. Notable and numerous differences were seen in genes coding for neuronal function, the extracellular matrix and cytoskeleton. In addition to producing functional networks, differentiated human neural stem cells grown in inert scaffolds offer several significant advantages over conventional 2D monolayers. These advantages include cost savings and improved physiological relevance, which make them better suited for use in the pharmacological and toxicological assays required for development of stem cell‐based treatments and the reduction of animal use in medical research. Copyright © 2015 John Wiley & Sons, Ltd.